What does illness teach? The experience of cancer as a life’s turning point - Ulaniecka, Natalia (Difficult situation in biographies: Volume 9, 2025)
The chapter discusses the issue of cancer as a problematic situation in biography, simultaneously a turning point and a catalyst for change. The main aspects related to the experience of cancer as a critical life event are presented, as well as the meaning attributed to it by (former) oncology patients in the context of self-reflection and life changes. The chapter includes patient quotes to illustrate how their self-perception and life values have changed. It also adresses the concept of posttraumatic growth and meaning-making focused coping.